Development of the Strategic Hospital of DKT Dr. Soetarto Yogyakarta - Dharma Putra, Ngurah Pradnya; ., Sabihaini; Mardiana, Tri (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
This study aims to develop the strategy Hospital DKT Dr Soetarto Yogyakarta to know the condition of the external and internal environment, alternative strategies, and priority strategies that can be done. This research is qualitative descriptive survey method. The development strategy is based on the concept of strategic management by using three stages: an input stage, using EFE matrix, IFE matrix, phase matching: using SWOT matrix, IE matrix, and the last stage is the stage of the decision to use a matrix QSPM. The data used is primary data obtained through observation, interviews and questionnaires, and secondary data from the archive documentation and medical records hospital. The results using IE matrix indicates the position of the hospital in a position to grow and build, so alternative strategies generated is incentive strategy and integration strategy, the SWOT matrix generates seven alternative strategies, and in the matrix QSPM, strategic priorities generated by the score allure total (STAS) is the highest obtained by the strategy of building partnerships with other bodies concerned with the improvement of health services.